Online Learning to Prevent the Spread of Pandemic Corona Virus in Indonesia - Henny Yulia (Universitas PGRI Semarang, 2020)
In March 2020 almost all cities in Indonesia face the scary viruses namely corona. The speed of the viruses spread influences all aspects of life without exception. Education system is one of the crucial things which is influenced by this virus. Whether want or not, the educators must change their way of teaching. Face to face in the class must be avoided. The purpose of this study is to clarify ways of corona virus pandemic reshape education. This study also explains about kinds of online learning which are used by the educators in the era of pandemic corona viruses in the world and the strategies to improve online teaching when university is closed. The advantages of using them are also clarified. In addition, the writer try to gain the information about the effectiveness of using online learning to teach.